O dicionário escolar como material didático facilitador da aprendizagem: em busca de uma aplicação efetiva em sala de aula - Patricia Ravagnani Despato (2021)
As we defend the pedagogical importance that the dictionary has, which can provide the student with the improvement of discursive practices, this research is developed. With a focus on the effective use of dictionaries in the classroom, we elaborate Directed Activities (ATD) in order to enable the reduction of inappropriate uses of paronyms and also homophones non-homographs by students of the 5th grade of Elementary School. For that, we established as a general objective: to develop a research whose result aims to enable the effective use of the monolingual school dictionary, with a view to reducing orthographic and semantic mistakes in the writing of students in the 5th grade of Elementary School, and the following specific objectives: i) to lecture on the importance of the school dictionary as a didactic material that facilitates the teaching - learning process of Portuguese as native language, to mitigate inappropriate uses of the lexicon; ii) to discuss the importance of lexical competence in teaching and learning Portuguese as a mother tongue, focusing on paronyms and homophones non- homographs; iii) to identify and inventory of the orthographic and semantic mistakes related to the uses of paronyms and homophones non-homographs more frequent in the writing of the 5th grade students of a public school in Três Lagoas / MS, through a questionnaire designed for this purpose; iv) elaborate ATD proposals that have the dictionary as the main source of consultation to be used during the accomplishment of the pedagogical activities and according to the needs of the students. For that, we are guided by the theoretical and methodological principles of Pedagogical Lexicography and by studies that deal with Vocabulary Teaching. As a first step, a verification activity was developed and applied, focusing on the paronyms and homophones non-homographs lexical units. After the application of the activity, the data survey was carried out, organizing the inventory of the most recurrent problems in the writing of the students participating in the research. Based on the inventory, ATD proposals were developed aiming at the dictionary to be explored effectively, expanding the students 'lexical competence and, thus, allowing the reduction of inappropriate uses of paronyms and non-homograph homophones in the students' writing. The ATD proposals were organized in two categories, one with a view to developing the students' ability to use the dictionary, and the other, with the purpose of offering activities that explore the didactic potential of the dictionary in the teaching and learning process, especially for the expansion of the students' lexical repertoire, and, consequently, of reading and writing. Keywords: Pedagogical Lexicography. Written production. Vocabulary Teaching.